Z-nucleic acids in virus-host interactions - Liverpool, L (2019)
One of the biggest threats faced by cells is infection. When a virus infects a cell, its nucleic acids can be recognised by cellular sensors, which activate potent antiviral innate immune responses, such as interferons and cell death. These initial responses are vital in preventing the spread of infection to surrounding cells. Critically, nucleic acid sensors must have mechanisms of recognising foreign, aberrant or mislocalised nucleic acids and distinguishing them from unperturbed cellular nucleic acids. Alternative conformations of nucleic acids may represent a molecular sign of virus infection that can be sensed. Double-stranded DNA and RNA can adopt different helical conformations, including the unusual Zconformation. The existence of proteins containing Z-binding domains (ZBDs) suggests Z-nucleic acids have important but so far poorly characterised biological functions. One such protein is Z-DNA binding protein-1 (ZBP1/DAI/DLM1). Using mouse cytomegalovirus as a model, we demonstrated that ZBP1 mediates virusinduced necroptotic cell death in a manner dependent on its two ZBDs. This suggests that the trigger for ZBP1 may be a Z-conformation nucleic acid. Knock-in mice, in which the ZBDs of ZBP1 are mutated, were more susceptible to virus infection. In addition to these mouse studies, we have demonstrated that ZBP1 also activates ZBD-dependent necroptosis in human cells and established and validated an assay for screening of small molecule or viral protein antagonists of ZBP1- mediated necroptosis in a human cell line.